2020
DOI: 10.1038/s41419-020-02987-9
|View full text |Cite
|
Sign up to set email alerts
|

Four-octyl itaconate activates Nrf2 cascade to protect osteoblasts from hydrogen peroxide-induced oxidative injury

Abstract: Four-octyl itaconate (4-OI) is the cell-permeable derivative of itaconate that can activate Nrf2 signaling by alkylating Keap1’s cysteine residues. Here, we tested the potential effect of 4-OI on hydrogen peroxide (H2O2)-induced oxidative injury in osteoblasts. In OB-6 cells and primary murine osteoblasts, 4-OI was able to activate Nrf2 signaling cascade and cause Keap1–Nrf2 disassociation, Nrf2 protein stabilization, cytosol accumulation, and nuclear translocation. 4-OI also augmented antioxidant-response ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 44 publications
6
56
0
Order By: Relevance
“…The mechanisms for anti-inflammatory effects of itaconate have been reported to involve the inhibition of succinate dehydrogenase, 26 , 56 blockade of IκBζ translation, 57 and activation of NRF2. 39 Although our data support the idea of itaconate-induced Nrf2/Ho-1 antioxidant signaling in exerting protective effects, 39 , 58 , 59 recent studies report distinct mechanisms for endogenous itaconate versus its derivatives in regulating inflammation. 35 , 36 The itaconate derivative OI reduces inflammation by triggering electrophilic stress, which is compensated by activation of the antioxidant Nrf2/Ho-1 axis, whereas endogenous itaconate evokes NRF2-independent mechanisms.…”
Section: Discussionsupporting
confidence: 45%
“…The mechanisms for anti-inflammatory effects of itaconate have been reported to involve the inhibition of succinate dehydrogenase, 26 , 56 blockade of IκBζ translation, 57 and activation of NRF2. 39 Although our data support the idea of itaconate-induced Nrf2/Ho-1 antioxidant signaling in exerting protective effects, 39 , 58 , 59 recent studies report distinct mechanisms for endogenous itaconate versus its derivatives in regulating inflammation. 35 , 36 The itaconate derivative OI reduces inflammation by triggering electrophilic stress, which is compensated by activation of the antioxidant Nrf2/Ho-1 axis, whereas endogenous itaconate evokes NRF2-independent mechanisms.…”
Section: Discussionsupporting
confidence: 45%
“…Furthermore, they also found that DI did not have the same effect on osteoclast function indicate that general electrophilic stress was probably not sufficient to induce the inhibition of osteoclastogenesis. In another research Zheng et al ( 2020 ) found 4-OI protected OB-6 cells and primary murine osteoblasts from oxidative injury, cell death, and apoptosis treated by H 2 O 2 through disassociation of Keap1 and Nrf2.…”
Section: The Candidate Mechanisms Of Itaconatementioning
confidence: 98%
“…Finally, 4-OI has emerged as an anti-inflammatory compound with utility in various disease models via activation of Nrf2 (Li et al, 2020;Liu et al, 2021;Olagnier et al, 2018;Olagnier et al, 2020;Zheng et al, 2020). Importantly, 4-OI represses interferon signaling both in response to viral stimuli and in cases of type I interferonopathies (Olagnier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%